(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The basis of treatment for Charcot neuroarthropathy is long-term immobilization in the form of a plaster cast or corset, as well as the use of antiresorptive drugs in the acute stage. However, some patients already have a disabling deformity or severe instability at the time of presentation for whom conservative treatment is doomed to failure. Although conservative treatment using TCC followed by appropriate bracing and footwear is considered the gold standard treatment for NS, surgical treatment is necessary when conservative treatment is ineffective. Surgery includes exostectomy, Achilles tendon lengthening, and arthrodesis.